A PERCEPÇÃO DOS ALUNOS DO ENSINO FUNDAMENTAL SOBRE A EXPERIMENTAÇÃO NAS AULAS DE CIÊNCIAS - Kinalski, Alvina C.; Afonso, Marcelo V.; Goettems, Pauline B.; Rosin, Catiusa K.; Hochmüller, Laura H. L. (Salão do Conhecimento, 2013)
Resumo